1997
DOI: 10.1111/j.1365-2222.1997.tb01239.x
|View full text |Cite
|
Sign up to set email alerts
|

No release of histamine and substance P in capsaicin‐induced neurogenic inflammation in intact human skin in vivo: a microdialysis study

Abstract: Capsaicin-induced neurogenic activation does not involve the release of histamine from mast cells or detectable amounts of substance P release from sensory nerves in normal human skin in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…Our results demonstrate that in humans no such interaction seems to exist, because aprepitant neither increases nor inhibits capsaicin-induced vasodilation, whereas CGRP 8-37 clearly decreases the response to capsaicin. This confirms findings by Petersen et al (1997), who could detect neither SP nor histamine release after intradermal capsaicin administration to humans. We therefore suggest that, in humans, SP has no major role in capsaicin-induced vasodilation.…”
Section: Mediators Of Capsaicin-induced Dermal Vasodilation 251supporting
confidence: 80%
“…Our results demonstrate that in humans no such interaction seems to exist, because aprepitant neither increases nor inhibits capsaicin-induced vasodilation, whereas CGRP 8-37 clearly decreases the response to capsaicin. This confirms findings by Petersen et al (1997), who could detect neither SP nor histamine release after intradermal capsaicin administration to humans. We therefore suggest that, in humans, SP has no major role in capsaicin-induced vasodilation.…”
Section: Mediators Of Capsaicin-induced Dermal Vasodilation 251supporting
confidence: 80%
“…Because of the mast cells' content of several inflammatory mediators and their presence in the vicinity of sensory nerve cells, the mast cells are likely to participate in neurogenic inflammation. A number of studies (5,17,24) have suggested a role for mast cells in the development of edema after neuropeptide challenge, but the ability to release histamine on neuropeptide stimulation seems to vary between species and different mast cell types. Nevertheless, activation of mast cells is associated with anaphylaxis in rats (23) and has been shown to lower P if in both the trachea of rats (15) and skin of both rats and mice (12,20).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the involvement of mast cells are the findings that stimulation of the rat saphenous nerve induces mast cell degranulation (27) and that SP in high concentrations (40) as well as topical application of capsaicin (7) induce cutaneous mast cell degranulation in human forearm. In contrast, Petersen et al (32) detected no release of SP and histamine after capsaicin injection in the same area.…”
mentioning
confidence: 88%
“…Although mast cells express SP receptors, their involvement in neurogenic inflammation has been debated. Neuropeptides can induce histamine release in a number of tissues (12,13,23,29), but it has been questioned whether endogenously released neuropeptides are present in sufficient amounts to induce mast cell activation and subsequent histamine release in human skin (22,32,40).…”
Section: Discussionmentioning
confidence: 99%